The Russian Lenguage, Culture and Mentality from the Hungarians' Standpoin - I. Bakoni (Russian State Vocational Pedagogical University, 2015)
The paper looks at the cross-cultural communication problems - one of the most significant educational issues, given the globalization processes and economic and scientific integration. In Hungary, the interest to learning the Russian language and culture is increasing as the way for understanding the potential international partner and strengthening the business relations between Hungary and Russia. In author's opinion, the unbiased information on the current situation in Russia and the history of relations between the two countries should stimulate the motivation for learning Russian as the second and third foreign language in Hungarian educational institutions. The retrospective analysis of the above relations demonstrates both the positive and negative trends, the latter being caused by the stereotypes influenced by the certain political powers and historical events. The paper empha- sizes the reasons behind the existing prejudices and myths concerning Russia. The author believes that such misjudgments should be persuasively corrected by the experts in the Russian language and culture, and regards this task as the first priority. In conclusion, the paper provides the brief review of the recent Hungarian publications on the comparative culture studies.